Hydrocarbation of CC Bonds: Quantification of the Nucleophilic Reactivity of Ynamides1. Issue 19 (8th April 2014) - Laub, Hans A.; Evano, Gwilherm; Mayr, Herbert
Abstract Donor‐substituted diarylcarbenium ions Ar2CH+ react with ynamides to give 1‐amido‐substituted allyl cations (α, β‐unsaturated iminium ions). Kinetic studies show that these adducts, which correspond to the addition of a CH bond across the CC bond, are formed stepwise with initial formation of keteniminium ions and subsequent 1, 3‐hydride shifts. The linear correlations between the second‐order rate constants (lg k2, 20 °C) with the electrophilicity parameters E of the diarylcarbenium ions allow us to include ynamides in our comprehensive nucleophilicity scale and thus predict potential electrophilic reaction partners.